Relación entre ansiedad y bienestar psicológico en adultos durante la pandemia por COVID-19 - Vasquez Cardoza, Daniela Violeta (2022)
The COVID-19 pandemic is an unprecedented event that has caused a global crisis in the field of mental health. Specifically, anxiety levels have increased significantly, affecting the population’s psychological well-being around the world. The objective of this study is to identify the relation between anxiety and psychological well-being in adults during the COVID- 19 pandemic. An applied review of related studies was carried out according to the PRISMA guide criteria (Urrútia & Bonfill, 2010). The databases consulted were Scopus, Scielo and Web of Science. After a literature review, ten articles were selected considering the aforementioned variables during the years 2020-2022. The selected studies were mostly correlational and cross sectional. After a thorough review, the results show that both variables have a negative relation in different samples around the world, namely, high levels of anxiety and low levels of psychological well-being. It should be noticed that the COVID-19 pandemic has not concluded, so it would be suitable to carry out studies in Peru to try to find solutions that mitigate the negative effects on the population's mental health.